2010
DOI: 10.1128/aem.02667-09
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Rare Specific Flavonoids on Compatible and Incompatible Strains in the Myrica gale - Frankia Actinorhizal Symbiosis

Abstract: Plant secondary metabolites, and specifically phenolics, play important roles when plants interact with their environment and can act as weapons or positive signals during biotic interactions. One such interaction, the establishment of mutualistic nitrogen-fixing symbioses, typically involves phenolic-based recognition mechanisms between host plants and bacterial symbionts during the early stages of interaction. While these mechanisms are well studied in the rhizobia-legume symbiosis, little is known about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…These results would suggest that the root exudates influence Frankia physiology by affecting cellular components beyond total protein levels. Our results with aqueous root exudates confirm previous studies on flavonoid effects on the growth of Frankia with methanol extracts or purchased phenolics (25,29,37). Although aqueous root exudates alone did not support Frankia growth, plant compounds in the root exudates enhanced the growth of Frankia.…”
Section: Production Of Aqueous Root Exudates and General Propertiessupporting
confidence: 81%
See 2 more Smart Citations
“…These results would suggest that the root exudates influence Frankia physiology by affecting cellular components beyond total protein levels. Our results with aqueous root exudates confirm previous studies on flavonoid effects on the growth of Frankia with methanol extracts or purchased phenolics (25,29,37). Although aqueous root exudates alone did not support Frankia growth, plant compounds in the root exudates enhanced the growth of Frankia.…”
Section: Production Of Aqueous Root Exudates and General Propertiessupporting
confidence: 81%
“…The soil-and axenically grown C. cunninghamiana root exudates contained similar levels of phenolic (2.0 to 4.9 g/ml) and flavonoid (9.9 to 18.6 g/ml) compounds (data not shown). Flavonoid compounds have been identified from extracts of Alnus glutinosa, Myrica gale, and Casuarina glauca (1,29). Although flavonoid compounds were detected in the C. cunninghamiana root exudates, we did not want to exclude other possible plant-signaling molecules and used aqueous extracts throughout this study.…”
Section: Production Of Aqueous Root Exudates and General Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the flavonoid-like compounds extracted from red alder (Alnus rubra), one possible flavanone enhanced nodulation, whereas two other compounds were shown to act as inhibitors (Benoit and Berry 1997). To assess the roles of flavonoids in Frankia-actinorhizal symbiosis, eight flavonoid compounds were extracted from the fruits of Myrica gale, with two dihydrochacone compounds found to enhance the growth and nitrogen fixation of compatible, but not incompatible, Frankia strains (Popovici et al 2010). Transcriptome analysis revealed that genes involved in flavonoid synthesis and auxin transport were activated in the roots of C. glauca, suggesting the important roles of flavonoids and auxin during the Frankia infection process and nodule organogenesis (Hocher et al 2011).…”
Section: Interaction With Rhizobiamentioning
confidence: 99%
“…43 Mb for the narrow-host-range Frankia strain CcI3 to 7.50 Mb for the medium-host-range Frankia strain ACN14a (ACN) to 8.98 Mb for the broad-host-range Frankia strain EAN1pec (EAN). Since the elucidation of these Frankia genomes, bioinformatic approaches have illuminated codon usage patterns (47), predicted secretosome profiles (35), and led to genomeguided studies on the Frankia transcriptome (3,44) and proteome (1,5,33,34). Genome mining also provides an opportunity to identify important physiology and metabolic functions, including secondary metabolism.…”
mentioning
confidence: 99%